The Characteristic of the Legal Competence of the Head of an Educational Institution in the Context of Managerial Competence - Iryna Darmanska (Pedagogical Discourse, 2013)
The article analyzes the content of legal competence of the head of an educational institution that is an integral component of his managerial competence. The legal competence of the head master is shown through the necessity of possessing of legal information with its reference to the educational and administrative activity. Legal competence of the manager of general educational establishment has to be formed be means of acquiring of the norms of law branches by the future specialist. Due to this the author reveals the content of the basic notions of constitutional, administrative, criminal, employment, family and international law with their binding to the educational sphere, in particular to the functioning of general educational establishment.